Increased mirror overflow movements in ADHD are associated with altered EEG alpha/beta band desynchronization. (30th December 2019) - McAuliffe, Danielle; Hirabayashi, Kathryn; Adamek, Jack H.; Luo, Yu; Crocetti, Deana; Pillai, Ajay S.; Zhao, Yi; Crone, Nathan E.; Mostofsky, Stewart H.; Ewen, Joshua B.
Abstract: Children with ADHD show developmentally abnormal levels of mirror overflow—unintentional movements occurring symmetrically opposite of intentional movements. Because mirror overflow correlates with ADHD behavioral symptoms, the study of disinhibition in motor control may shed light on physiologic mechanisms underlying impaired behavioral/cognitive control. This is a case–controlled study of EEG recording from 25 children with ADHD and 25 typically developing (TD) controls performing unilateral sequential finger tapping, with overflow movements measured using electronic goniometers. Consistent with previously published findings, children with ADHD showed increased mirror overflow as compared with TD peers. EEG findings revealed less lateralized alpha modulation (event‐related desynchronization; ERD) and decreased magnitude of beta ERD in ADHD; both alpha and beta ERD reflect cortical activation. Moderation analysis revealed a significant association between beta ERD and overflow, independent of diagnosis; and an equivocal ( p = .08) effect of diagnosis on the relationship between alpha ERD and overflow, with a significant effect in children with ADHD but not TD children. These results suggest two mechanisms involved with mirror overflow: one reflected in beta ipsilateral to the intentional movement and relevant to both children with ADHD and controls, and the other seemingly more specific to ADHD (alpha, contralateral to movement). Abstract : Children with ADHD have unexpectedly large amounts of involuntary movement in one hand when they voluntarily move the other hand. During a finger‐tapping task, children with ADHD showed atypical activation on EEG in two frequency bands, alpha and beta. Variability in beta activation was associated with involuntary movements in both controls and children with ADHD, whereas variability in alpha activity was relevant only in children with ADHD.